The influence of tax knowledge, tax awareness, and tax morality on tax compliance of MSMEs in the Kebon Bawang Urban Village, North Jakarta - Izdhihar, Rendy Farrel; Tarmidi, Deden (Educoretax, 2024)
This study aims to test and analyze the Influence of Tax Knowledge, Tax Awareness, and Tax Morality on Tax Compliance of MSME Taxpayers residing in the Kebon Bawang Village area, North Jakarta. This research method uses the Nonprobability sampling method using Accidental Sampling and using the Hair formula with a research sample of 100 respondents. The results of this study are (1) Tax knowledge does not have a positive effect on MSME taxpayer compliance. (2) Tax awareness has a positive effect on MSME taxpayer compliance. (3) Tax morality has a positive effect on MSME taxpayer compliance. The conclusion from the study indicates that tax knowledge does not influence SMEs taxpayers' compliance due to the lack of knowledge among SMEs taxpayers about the payment deadlines for their tax obligations.